A Si–SiC Oxidation‐resistant Coating for Carbon/Carbon Composites by Hot‐pressing Reaction Technique. Issue 2 (25th February 2013) - Fu, Qiangang; Cao, Cuiwei; Li, Hejun; Tao, Jun; Li, Kezhi
<x xml:space="preserve">Abstract</x> A Si–SiC coating was prepared by hot‐pressing reactive sintering (HPRS) technique for protecting carbon/carbon (C/C) composites against oxidation. The Si–SiC coating has a dense and crack‐free structure with a thickness of 70–90 μm. The Si–SiC coating by HPRS has a higher SiC content and lower Si content than the coating by pressure‐less reactive sintering (PRS). It also exhibits better oxidation‐protective ability than that prepared by PRS. With hot‐pressing, the flexural strength of the Si–SiC coated C/C composites decreases from 121 MPa to 99 MPa, and the interface bonding strength increases from 6 MPa to 10 MPa.